Unilateral Conversion of Minors to Islam: Legal Discourse and Muslim Converts’ Narrative on Custody and Religious Rights in Malaysia - Azlan Shah Nabees Khan; Mohd Al Adib Samuri (Kajian Malaysia, 2022)
The unilateral conversion of minors to Islam is a controversial issue in Malaysia, particularly when it involves conflicting legal rights between Muslim converts and their non-Muslim families regarding issues of parental rights, child custody and determination of the child’s religion. Even more pertinent is the fact that the issue of conversion is intertwined with legal and socio-political issues such as the rising Muslim religious conservatism, Islamisation of law and political identity. As such, this article aims to discuss the issues of parental rights, child custody and determination of the child’s religion in the context of conversion to Islam in Malaysia from a legal and Muslim convert’s perspective. To explore the perspective of Muslim converts on the matter, nine participants were interviewed for the purpose of this study and were recruited through the snowball method amongst activist converts and individuals who were involved in related court cases. This study found that the negotiations that have to be made by these converts demonstrate the pressure they face to prove their commitment to their new religion, all the while maintaining their family dynamic. To some converts, Islam and its terms are referenced in the negotiation process, whether through legal channels or through public discourse; further, there are more peaceful narratives that ensure the family dynamics and its integrity, despite the ultimate goal being a da’wah (proselytisation) agenda. Beyond Malaysia, this study shows how religious laws impact the lives of multiethnic and multireligious community